KAJIAN HADIS-HADIS TENTANG KOMODIFIKASI AIR PERSPEKTIF HERMENEUTIKA MAQȦŜIDỊ AL-SYẬṪIBỊ - Khanifa, Nurma Khusna; Sawaun, Sawaun (Al-Fath, 2021)
In the classical Islamic legal tradition (fiqh), water is widely discussed from the point of view as an instrument for purification (thaharah) and also as a material consumed, either by humans or livestock. This seems to be inseparable from the existence of hadith texts that prohibit making water as a traded commodity contained in various hadith master books. This prohibition arises because water is considered a basic need that is not allowed to be owned by certain individuals or groups. In fact, nowadays, water has become a commodity that has a very high selling value. This can be seen from the proliferation of mineral water brands on the market. In the perspective of al-Syibị's hermeneutics, water is an emergency need for dharûriyyah which is something essential and must exist for the realization of human welfare, both spiritually and materially. However, within certain limits, the commodification of water can still be allowed on the condition that the water source is included in a private area, even if in an emergency, access to water must be granted to everyone. According to al-Syibị the main purpose of the provisions of religious law is for the benefit of humans, both in the present life (world) and the life to come (the hereafter). Therefore, the determination of the law contained in the texts of the Qur'an and Sunnah is always based on ta`lịl, both globally and in detail.